Geologi dan Pengaruh Struktur Kekar Terhadap Kestabilan Lereng Desain Pit Pada Tambang Terbuka Batubara Kecamatan Lawang Kidul, Kabupaten Muaraenim, Sumatra Selatan - Riswandi, Herry; Fitri, Arnia (PROGRAM STUDI TEKNIK GEOLOGI FAKULTAS TEKNOLOGI MINERAL UPN VETERAN YOGYAKARTA, 2024)
Open pit mining system is one of the systems used to exploitation coal resources by stripping the overburden to produce slopes. Unstable slopes will result in landslides. Fractures are one of the causes of landslides. The purpose of the study was to determine the geological and geotechnical conditions of the area to create an optimal and safe slope design. The research area is administratively located in Tanjung Lalang, Lawang Kidul District, Muara Enim Regency, South Sumatra Province, which is a mining business permit (IUP) area of PT Bukit Asam Tbk. Geographically located at the geographical coordinates 103° 49'0